Preliminary design and performance estimate of a prime focus camera for the 2.3m Thai National Telescope - Weerapot Wanajaroen (2018)
© 2018 SPIE. The National Astronomical Research Institute of Thailand (NARIT) is currently developing a five lenses prime focus camera in order to enlarge the field of view of the 2.3 m Thai National Telescope to a one degree diameter circle. The instrument shall operate in the spectral bands B, V, R and I of the Johnson-Cousins photometric system with an angular resolution better than 2 arcsecond. In this paper, we describe the camera design, we estimate the theoretical performance in the V-band and we show that the theoretical angular resolution after tolerancing is better that 1.3 arcsecond. Then, we present the results of the stray light analysis and we show that the system is free of critical ghost images.